The changes of aortic stiffness during normal menstrual cycle - Amilia Aminuddin,; Luqman Hakim AZ,; Chan, SY; Nur Elyatulnadia S,; Hamizatul Akma H,; Nur Shahira Afifa R,; Ugusman A,; Chellappan C, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Pulse wave velocity (PWV), augmentation index (AI) and finger photoplethysmography fitness index (PPGF) are non-invasive markers of vascular function and may predict future cardiovascular disease (CVD) risk. In women, the changes from both oestrogen and progesterone levels during menstrual cycle may give significant impact on vascular function. Thus, this study was designed to investigate the variation of vascular function during follicular and luteal phase in healthy young women. Twenty-two healthy young women with regular menstrual cycle were recruited. Blood pressure (BP), body mass index (BMI), PWV, AI, PPGF, estradiol (Es) and progesterone (Prog) level were measured during follicular (F) and mid-luteal (L) phase. Data was analyzed via SPSS version 20 and P value < 0.05 was considered to be significant. The mean age of the subjects was 22.73 ± 0.60 years. There was significant variations of estradiol and progesterone levels during menstrual cycle whereby the level of estradiol (EsF = 107.6 ± 52.56 pmol/L vs. EsL = 555.16 ± 152.79 pmol/L, P<0.05) and progesterone (ProgF = 0.62 ± 0.26 nmol/L vs. ProgL = 46.74 ± 14.59 nmol/L, P<0.05) were higher in mid-luteal compared to follicular phase. PWV value was higher during follicular phase when compared to mid-luteal phase (PWVF = 6.67 ± 0.66 m/s vs. PWVL = 6.31 ± 0.52 m/s, P=0.01). The levels of BP, BMI, PPGF (PPGFF = 55.43 ± 7.50% vs. PPGFL = 56.59 ± 7.23 %, P=0.41) and AI (AIF = 12.87 ± 5.13% vs. AIL = 10.80 ± 4.52%, P=0.11) were unchanged between the two phases. In conclusion, PWV differs between follicular and mid-luteal phases of menstrual cycle in healthy young women. Thus, history of menstrual cycle must be taken into account when assessing PWV among women.